TRANSLATION, ADAPTATION, VALIDATION AND APPLICATION OF “PATIENTS’ PERCEPTION SAFETY CULTURE SCALE (PAPSCS)” IN AN EGYPTIAN SURGICAL INPATIENT HEALTHCARE SETTING - Abdel-Aziz, Basem Farouk (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Sundry studies are executed in high-income countries examining patient perceived safety culture (PaPSC) in healthcare settings. Paucity of analogous research in developing countries including Egypt is a motive behind this research pursuing translation, cross-cultural adaptation, reliability assessment, construct validation, and application of “Patients’ Perception Safety Culture Scale (PaPSCS)” in a surgical inpatient setting in Alexandria Main University Hospital.   Methods: Cross-sectional survey with a random sample of  is executed using a formally forwardly-backwardly Arabic translated version of PaPSCS. Elevenitemed PaPSCS is purified by eliminating three apparently ambiguous insufficiently loading items. Collected sample is randomly split into two equal subsamples, one for explorative purposes and the other for confirmation. Factor analysis via structural equation modelling is employed to construct-validate PaPSCS.